2016
DOI: 10.1093/femsyr/fow082
|View full text |Cite
|
Sign up to set email alerts
|

Candida glabrataencodes a longer variant of the mating type (MAT) alpha2 gene in the mating type-likeMTL3locus, which can form homodimers

Abstract: The fungal pathogen Candida glabrata is a haploid asexual yeast. Candida glabrata contains orthologs of the genes that control mating and cell-type identity in other fungi, which encode putative transcription factors localized in the MAT locus in Saccharomyces cerevisiae or MTL in other fungi. Candida glabrata contains three copies of the CgMTL locus but only CgMTL1 correctly expresses the information encoded in it. CgMTL1 can encode the Cg A1: gene ( A: information), or the Cgalpha1 and Cgalpha2 genes (alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The MAT locus in S. cerevisiae , consisting of the active MAT locus, and silent HMLα and HMRa loci, resides on the chromosome III (Figure 2), and the mating type is determined by the presence of MATa or MATα allele [75]. However, unlike S. cerevisiae , the MAT loci are present on different chromosomes in C. glabrata with CgMTL1 and CgMTL3 on chromosome B, and Cg MTL2 on chromosome E (Figure 2) [76]. CgMTL1 locus encodes either ‘a’ ( Cga1 gene) or ‘alpha’ ( Cgα1 or Cgα2 genes) information while CgMTL2 and CgMTL3 code for ‘a’ and ‘α’ information, respectively [74,76].…”
Section: Salient Pathobiological Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAT locus in S. cerevisiae , consisting of the active MAT locus, and silent HMLα and HMRa loci, resides on the chromosome III (Figure 2), and the mating type is determined by the presence of MATa or MATα allele [75]. However, unlike S. cerevisiae , the MAT loci are present on different chromosomes in C. glabrata with CgMTL1 and CgMTL3 on chromosome B, and Cg MTL2 on chromosome E (Figure 2) [76]. CgMTL1 locus encodes either ‘a’ ( Cga1 gene) or ‘alpha’ ( Cgα1 or Cgα2 genes) information while CgMTL2 and CgMTL3 code for ‘a’ and ‘α’ information, respectively [74,76].…”
Section: Salient Pathobiological Featuresmentioning
confidence: 99%
“…However, unlike S. cerevisiae , the MAT loci are present on different chromosomes in C. glabrata with CgMTL1 and CgMTL3 on chromosome B, and Cg MTL2 on chromosome E (Figure 2) [76]. CgMTL1 locus encodes either ‘a’ ( Cga1 gene) or ‘alpha’ ( Cgα1 or Cgα2 genes) information while CgMTL2 and CgMTL3 code for ‘a’ and ‘α’ information, respectively [74,76]. While CgMTL1 and CgMTL2 are transcriptionally active, CgMTL3 is subjected to subtelomeric silencing [77].…”
Section: Salient Pathobiological Featuresmentioning
confidence: 99%
“…glabrata mating‐type combinations did not exert any significant effects on the MICs of the tested antifungals, except for CAS and AFG, indicating that discovering spontaneous mating‐type switching, especially clinical isolates might be challenging. Robledo‐Marquez et al observed no changes in growth phenotype (colony size or morphology) under different stress conditions, that is FLU, NaCl, H 2 O 2 and metals, compared to C . glabrata strains expressing the a and α alleles generated in the laboratory, and MTL1 , MTL2 and MTL3 mutant isolates.…”
Section: Discussionmentioning
confidence: 98%
“…The strains were grown in YPD at 30°and harvested in stationary phase. The protein extraction and western blot assays were done as previously described with minor modifications (Orta-Zavalza et al 2013;Robledo-Márquez et al 2016). Briefly, cells were resuspended in lysis buffer [45 mM HEPES, 400 mM potassium acetate, 0.5% Nonidet P-40, 1 mM EDTA, 1 mM DTT, 1 mM PMSF, and 13 Complete protease inhibitor cocktail (Roche)], 100 ml of zirconia beads were added, and cells were broken using FastPrep-24 (MP Biomedicals) equipment, with three pulses for 60 sec at 6 m/sec.…”
Section: Western Blot Assaymentioning
confidence: 99%